Drug‐releasing Microspheres for Stem Cell Differentiation. Issue 12 (17th December 2021) - Sharma, Ruchi; Benwood, Claire; Willerth, Stephanie M.
Abstract: The ability of stem cells to differentiate into specialized cells make them a valuable tool for therapeutic applications. 3D bioprinting, a subset of additive manufacturing, uses bioinks composed of cells and biomaterials to create living tissues. The use of bioactive factors like small molecules and proteins can promote stem cell differentiation into the desired cell phenotypes for tissue regeneration. Small molecules can accelerate the process of regeneration in tissue engineering, maintain bioactivity in a biological environment, and minimize the costs associated with this process. Additionally, they can be encapsulated in specialized drug‐delivery devices called microspheres for controlled release. Microspheres are small (1‐1000 μm) spherical particles usually made from biodegradable and biocompatible polymers that can be loaded with drugs and other bioactive components. They can then be integrated into stem‐cell‐laden bioinks used to form bioprinted tissues, where they will release the encapsulated drug and promote differentiation of stem cells into the desired mature cell type. Microspheres can be widely used to encapsulate a broad range of therapeutic agents, including hydrophilic and hydrophobic small molecule drugs, DNA, and proteins. The release of encapsulated molecules occurs through degradation and erosion of the polymer matrix. This article provides detailed protocols for fabricating and sterilizing drug‐releasing microspheres made from poly‐ε‐caprolactone, a promising biodegradable polymer often used for controlled drug delivery due to its biocompatibility and biodegradation kinetics. Additional protocols describe characterization of the loading and size of microspheres as well as incorporation of microspheres into a fibrin‐based bioink for 3D bioprinting. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Fabrication of drug‐releasing PCL microspheres Support Protocol 1 : Preparation of microspheres for determination of encapsulation efficiency by HPLC Support Protocol 2 : Preparation of microspheres for SEM analysis Basic Protocol 2 : Incorporation of microspheres into fibrin‐based bioink